2006
DOI: 10.1088/0953-2048/19/11/009
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ti-sheathed MgB2wires with high critical current density

Abstract: Working towards developing lightweight superconducting magnets for future space and other applications, we have successfully fabricated mono-core Ti-sheathed MgB 2 wires by the powder-in-tube method. The wires were characterized by magnetization, electrical resistivity, x-ray diffraction, scanning electron microscopy, and energy dispersive spectrometry measurements. The results indicate that the Ti sheath does not react with the magnesium and boron, and the present wire rolling process can produce MgB 2 wires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Recently, titanium as a sheath material has been used for single-core MgB 2 wires by Serquis and Alessandrini et al [9,10]. They did not observe any reaction or diffusion up to 900 • C and the manufacturing process for titanium grade 2 was similar to that used for iron sheathed wires [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, titanium as a sheath material has been used for single-core MgB 2 wires by Serquis and Alessandrini et al [9,10]. They did not observe any reaction or diffusion up to 900 • C and the manufacturing process for titanium grade 2 was similar to that used for iron sheathed wires [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have successfully fabricated Ti-sheathed, undoped MgB 2 wires with high J c and demonstrated that the performance of a Ti-sheath on J c is comparable to or even better than an Fe-sheath [15]. To further increase J c for future applications of Ti-sheathed MgB 2 wires in lightweight superconducting magnets, we fabricated Ti-sheathed MgB 2 wires doped with crystalline nano-SiC (20 nm) at different doping levels.…”
Section: Introductionmentioning
confidence: 99%
“…We also reported the effect on Ti-sheathed MgB 2 wires dual doped with nanosized rare-earth oxides and SiC. Our selection of titanium as sheath material was based on the following facts: (1) the performance of Ti-sheathed wires is comparable to or even better than iron-sheathed wires [21]; (2) the magnetic measurement is much easier on Ti-sheathed wire than ferromagnetic metal sheathed wire.…”
Section: Introductionmentioning
confidence: 99%